Efectos de la fertilización de Boro y Zinc, en el rendimiento del cultivo de maíz (Zea mays L.), en la zona de Babahoyo - Anchundia Huacon, Nelson Humberto (2018)
VII. SUMMARY The present experimental work was carried out in the lands of Mr. Vicente Jiménez Carbo, located in the Rcto. New Town of Febres Cordero Parish of Babahoyo Canton. The Insignia 105 corn hybrid was used as seed material. The objectives were to determine the effects of Boron and Zinc in the increase of corn yield; identify the Boron and Zinc levels that most influence crop yield and economically analyze the treatments under study. The present experimental work consisted of treatments with Boroned 0.5 and 1.0 L / ha; Ned zinc 0.5 and 1.0 L / ha; Boroned + Ned zinc 0.5 + 0.5; 1.0 + 1.0; 0.5 + 1.0; 1.0 + 0.5 L / ha applied at 15 and 25 days after sowing and a control treatment (conventional Fertilization) with a dose of 140 kg N; 80 kg P, 90 kg K. The experimental design of Complete Blocks at Random was used with 9 treatments and 3 repetitions, to perform the evaluation of the means of the treatments, the analysis of variance was used and the comparison of means was made with the Duncan test at 5% of probability. To estimate the effects of the treatments, the data of leaf analysis, plant height, days to flowering, height of ear insert, diameter and length of ear, number of grains per ear, grain - tusse relation, weight of 1000 grains, crop yield and economic analysis. Based on the results obtained, it was determined that the use of Boroned + Ned zinc at a dose of 0.5 + 0.5 L / ha, applied 20 days after sowing, Boroned + Ned zinc doses of 0.5 + 0.5 L / ha at 20 dds exceeded the averages with 6274.4 kg / ha and higher net profit with $ 213.3. The boron and zinc content in the leaves was variable, boron tended to increase the foliar content but its values were lower than the adequate level. Zinc was not increased because it seems that the soil has an important content for the development of corn.